Noise-Induced Hearing Loss in Professional Orchestral Musicians - Małgorzata PAWLACZYK-ŁUSZCZYNSKA; Małgorzata ZAMOJSKA; Adam DUDAREWICZ; Kamil ZABOROWSKI (Archives of Acoustics)
The overall purpose of this study was to assess hearing status in professional orchestral musicians. Standard pure-tone audiometry (PTA) and transient-evoked otoacoustic emissions (TEOAEs) were per- formed in 126 orchestral musicians. Occupational and non-occupational risk factors for noise-induced hearing loss (NIHL) were identified in questionnaire inquiry. Data on sound pressure levels produced by various groups of instruments were also collected and analyzed. Measured hearing threshold levels (HTLs) were compared with the theoretical predictions calculated according to ISO 1999 (1990). Musicians were exposed to excessive sound at weekly noise exposure levels of for 81–100 dB (mean: 86.64.0 dB) for 5–48 years (mean: 24.010.7 years). Most of them (95%) had hearing corresponds to grade 0 of hearing impairment (mean hearing threshold level at 500, 1000, 2000 and 4000 Hz lower than 25 dB). However, high frequency notched audiograms typical for noise-induced hearing loss were found in 35% of cases. Simultaneously, about 35% of audiograms showed typical for NIHL high frequency notches (mainly occurring at 6000 Hz). When analyzing the impact of age, gender and noise exposure on hearing test results both PTA and TEOAE consistently showed better hearing in females vs. males, younger vs. older musicians. But higher exposure to orchestral noise was not associated with poorer hearing tests results. The musician’s audiometric hearing threshold levels were poorer than equivalent non-noise-exposed population and better (at 3000 and 4000 Hz) than expected for noise-exposed population according to ISO 1999 (1990). Thus, music impairs hearing of orchestral musicians, but less than expected from noise exposure.